Sex‐specific population dynamics and demography of capercaillie (Tetrao urogallus L.) in a patchy environment. Issue 1 (27th November 2019) - Augustine, Ben C.; Kéry, Marc; Olano Marin, Juanita; Mollet, Pierre; Pasinelli, Gilberto; Sutherland, Chris
Abstract: Modeling the population dynamics of patchily distributed species is a challenge, particularly when inference must be based on incomplete and small data sets such as those from most species of conservation concern. Here, we develop an open population spatial capture–recapture (SCR) model with sex‐specific detection and population dynamics parameters to investigate population trend and sex‐specific population dynamics of a capercaillie ( Tetrao urogallus ) population in Switzerland living in eight distinct forest patches totaling 22 km 2 within a region of 908 km 2 and sampled via scat collection. Our model accounts for the patchy distribution of habitat and the uncertainty introduced by collecting data only every third year, while producing sex by patch population trajectories. The estimated population trajectory was a decline of 2% per year; however, the sex specificity of the model revealed a decline in the male population only, with no evidence of decline in the female population. The decline observed in males was explained by the demography of just two of the eight patches. Our study highlights the flexibility of open population SCR models for assessing population trajectories through time and across space and emphasizes the desirability of estimating sex‐stratified population trends especially in species of conservation concern. Abstract : We used novel sex‐specific open population spatial capture–recapture models to estimate capercaillie population dynamics across a patchy landscape. While the overall population trajectory indicated a declining population, we were able to determine the decline occurred only in the male population and in two of the eight habitat patches. This study provides information critical for the conservation of this species and highlights the flexibility and utility of open population capture–recapture models.